Comparative study of flexural strength and elasticity modulus in two types of direct fiber-reinforced systems - Alfredo de Aquino Gaspar Junior; Manuela Wanderley Ferreira Lopes; Gabriela da Silveira Gaspar; Rodivan Braz (Sociedade Brasileira de Pesquisa Odontológica, 2009)
The objective of this study was to compare the flexural strength and elasticity modulus of two types of staple reinforcement fibers, Interlig - Ângelus®/glass (Londrina, PR, Brazil) and Connect - KerrLab®/polyethylene (MFG Co., West Collins Orange, CA, USA), which are widely used in Dentistry for chairside use, after varying the number of layers employed and submitting or not to thermocycling. This study was performed on 72 specimens, divided into 8 groups: G1 - single layer of Interlig fibers without thermocycling; G2 - double layer of Interlig fibers without thermocycling; G3 - single layer of Interlig fibers with thermocycling; and G4 - double layer of Interlig fibers with thermocycling; G5 - single layer of Connect fibers without termocycling; G6 - double layer of Connect fibers without termocycling; G7 - single layer of Connect fibers with termocycling; G8 - double layer of Connect fibers with termocycling. For each group, values for flexural strength and elasticity modulus were obtained. The polyethylene fiber employed in a double layer presented the highest flexural strength (p < 0.05), independently of thermocycling (p < 0.001), when compared to the other evaluated combinations. The polyethylene fiber, used in a single layer without thermocycling, demonstrated a significantly higher elasticity modulus, when compared to the other groups (p < 0.05). Within the limits of this study, it was concluded that the polyethylene fiber in a double layer appears to be more resistant, regardless of whether it was submitted to thermocycling or not.